Genes and neural circuits for sleep of the fruit fly. - Tomita, J.; Ban, G.; Kume, K. (Neuroscience Research, 2017)
Sleep is a universal physiological state evolutionarily conserved among species, but the molecular basis for its regulation is still largely unknown. Due to its electroencephalogram criteria, sleep has long been investigated and described mostly in mammalian species. The fruit fly, Drosophila melanogaster, has emerged as a genetic model organism for studying sleep. The Drosophila sleep is behaviorally defined, and is tightly regulated by circadian and homeostatic processes, like mammals. Genetic analyses using Drosophila have successfully identified a number of conserved regulatory mechanisms underlying sleep between flies and mammals. Identification of sleep-regulating neural circuits is required to further elucidate these molecular mechanisms. Two major brain regions, the mushroom bodies and the central complex, play crucial roles in sleep regulation in Drosophila. Noteworthy, many detailed studies on neural circuits in these brain regions have clearly shown that specific small group of neurons are implicated in sleep homeostasis. Thus, recent progress in Drosophila sleep provides novel insights into understanding the molecular and neural basis of sleep.